Design and Simulation of Photo-excited Tunable Perfect Absorber Based on Semiconductor-incorporated Metamaterial Structure. Issue 1 (1st April 2022) - Ge, Tingting; Li, Zhijin; Song, Wei; Sheng, Xinqing
Abstract: The perfect metamaterial absorber with sandwich structure is capable to realize nearly 100% microwave absorption. We designed and simulated a photo-excited tunable perfect absorber based on semiconductor-incorporated metamaterials using HFSS (Ansoft). This absorber composes of semiconductor Ge in designed pattern in the unit cell. Under different pump power of the incident laser light, the conductivity of Ge on the metamaterial varies. In this way, the absorption frequency of the absorber can be tuned. Simulation results showed that, under the two pump light conditions, the absorber is with maximum absorbances of over 97% in both cases. We also analyzed the loss in the absorber through numerical experiments.